2010
DOI: 10.1080/09540120903431330
|View full text |Cite
|
Sign up to set email alerts
|

Assessing male spousal engagement with prevention of mother-to-child transmission (pMTCT) programs in western Kenya

Abstract: The importance of male spousal involvement in the prevention of mother-to-child transmission (pMTCT) programs is incremental to maintain family health and adherence to human immunodeficiency virus (HIV) treatment and prevention regimens. This study examined reasons for men's involvement in pMTCT initiatives sought by their wives and other HIV-related services in western Kenya. Data were collected from 146 men and women during 16 focus groups across four different HIV-related clinics. Four different groups of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 14 publications
11
83
0
Order By: Relevance
“…The finding is consistent with a cross-sectional study done in Kibaale District, Uganda [7], a cross-sectional study done in eastern Uganda [9] and Kenya [21,22] which showed level of male involvement in the ANC/PMTCT was 16%, 15% and 15% respectively. But it is not supported by the study conducted in Northern Ethiopia, Mekele which revealed the level of male partner involvement in ANC/PMTCT services was 20% [6].…”
Section: Discussionsupporting
confidence: 90%
“…The finding is consistent with a cross-sectional study done in Kibaale District, Uganda [7], a cross-sectional study done in eastern Uganda [9] and Kenya [21,22] which showed level of male involvement in the ANC/PMTCT was 16%, 15% and 15% respectively. But it is not supported by the study conducted in Northern Ethiopia, Mekele which revealed the level of male partner involvement in ANC/PMTCT services was 20% [6].…”
Section: Discussionsupporting
confidence: 90%
“…This would affect income-generating activities. Long waiting times at the health facility have been reported to deter the participation of men in maternal and child health services [13,21]. These studies have reported that in most of the health facilities in low- and middle-income countries, women spend a long time waiting for the ANC services, mainly due to a shortage of health providers.…”
Section: Discussionmentioning
confidence: 99%
“…Documented barriers to MPI include poor communication within couples (Ditekemena et al, 2012;Kalembo, Yukai, Zgambo, & Jun, 2012;Reece, Hollub, Nangami, & Lane, 2010), less stable relationship status (Larsson et al, 2010;Morfaw et al, 2013) and traditional gender roles (Nkuoh et al, 2010;Reece et al, 2010;Theuring et al, 2009), including the belief that antenatal care is purely a women's responsibility.…”
Section: Introductionmentioning
confidence: 99%